AgileMood: A Tool for Ongoing Measurement of Psychological Safety in Agile Teams - Melo, Arthur M. B.; Marinho, Marcelo; Sampaio, Suzana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2025)
Psychological safety and individual emotions have proven essential for the effective functioning of agile teams, directly impacting collaboration, collective performance and ultimately, software quality. This paper presents AgileMood, a tool designed to diagnose and enhance psychological safety and emotional awareness in agile teams through the collection of periodic anonymous feedback, the calculation of specific metrics, and the generation of dynamic visualizations. The solution not only measures the overall perceived level of safety and emotions but also detects internal variations among team members, enabling data-driven interventions. Agile-Mood distinguishes itself from existing approaches by incorporating well-established theoretical foundations, preserving anonymity, and offering practical support for decision-making by team leaders. The empirical evaluation of the tool, conducted through a case study involving 41 students (7 teams of 5 to 8 team members), utilized the System Usability Scale (SUS) and the Technology Acceptance Model (TAM), demonstrating promising usability and high perceived usefulness. Available as open-source software, the tool facilitates replicability and further development by the community. As a contribution, this work proposes a practice-oriented artifact with the potential to transform psychological safety and emotions into a measurable and manageable element within agile software development teams, thereby fostering improved software quality. Future studies should empirically evaluate its application in real organizational contexts.